Assessing final year undergraduate student teacher on school based teaching practice at the Polytechnic of the University Malawi: a dual assessment process - Elias Kaphesi (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2013)
The present study was an evaluation of assessment of fourth year undergraduate student teachers on teaching practice in secondary schools. The study was carried out in the Department of Mathematics and Statistics at the Malawi Polytechnic of the University of Malawi. A total number of 18 (14 males, 4 females) mathematical sciences education students of the Polytechnic of the University of Malawi were included in the study. The assessment grades and supervision comments were taken by using instruments designed and approved by the department. All the measurements were taken by observing a student teacher planning and delivering a lesson as part of a requirement of the degree of bachelor of education in mathematical sciences education of the University of Malawi. Obtained data was analysed and attempt was made to find out correlation between assessment grade and the supervision comments based on the observed lesson. A positive correlation of grades was observed with the comments made and that the grade given to each individual student was lower than what the comments suggests regarding the quality of the student.  The results raise the question of the validity and authenticity of assessment and supervision conducted by teacher educators. The results of the present study would be useful for teacher trainers/educators involved in assessing and supervising students during teaching practices.